Identification of mVOCs from Andean Rhizobacteria and Field Evaluation of Bacterial and Mycorrhizal Inoculants on Growth of Potato in its Center of Origin - Kromann, P. (2017)
Food security (a pressing issue for all nations) faces a threat due to population growth, land availability for growing crops, a changing climate (leading to increases in both abiotic and biotic stresses), heightened consumer awareness of the risks related to the use of agrichemicals, and also the reliance on depleting fossil fuel reserves for their production. Legislative changes in Europe mean that fewer agrichemicals will be available in the future for the control of crop pests and pathogens. The need for the implementation of a more sustainable agricultural system globally, incorporating an integrated approach to disease management, has never been more urgent. To that end, the Valorizing Andean Microbial Diversity (VALORAM) project (http://valoram.ucc.ie), funded under FP7, examined the role of microbial communities in crop production and protection to improve the sustainability, food security, environmental protection, and productivity for rural Andean farmers. During this work, microbial volatile organic compounds (mVOCs) of 27 rhizobacterial isolates were identified using gas chromatography/mass spectrometry (GC/MS), and their antifungal activity against Rhizoctonia solani was determined in vitro and compared to the activity of a selection of pure volatile compounds. Five of these isolates, Pseudomonas palleroniana R43631, Bacillus sp. R47065, R47131, Paenibacillus sp. B3a R49541, and Bacillus simplex M3-4 R49538 trialled in the field in their respective countries of origin, i.e., Bolivia, Peru, and Ecuador, showed significant increase in the yield of potato. The strategy followed in the VALORAM project may offer a template for the future isolation and determination of putative biocontrol and plant growth-promoting agents, useful as part of a low-input integrated pest management system.